CBMT-17. DEFECTIVE QKI-DEPENDENT LIPID METABOLISM INDUCES GENOMIC INSTABILITY AND SENSITIZES GLIOBLASTOMA TO IMMUNOTHERAPY - Shingu, Takashi (Neuro Oncol, 2019)
Despite transformative effects on the therapy of cancers such as melanoma and lung adenocarcinoma, blockade of the T cell immune checkpoints has generated limited impact on glioblastoma. Identifying genetic/genomic alterations that could potentially sensitize the patients to immunotherapy will significantly improve the efficacy of immunotherapy on glioblastoma patients. As part of our effort to identify novel glioma suppressors that affect the interaction of GSCs with their microenvironment, we discovered that the RNA-binding protein Quaking (QKI) is a key regulator of cellular endocytosis. QKI is mutated or deleted in ~34% of human glioblastomas. Supporting QKI’s tumor suppresser function, 92% of the Nestin-CreERT2;Qki(L/L);Pten(L/L);p53(L/L) mice developed glioblastoma with a median survival of 105 days, however, the Nestin-CreERT2;Pten(L/L);p53(L/L) mice did not develop any glioma up to a year. Mechanistically, QKI regulates the RNA stability and alternative splicing of numerous protein and lipid components of endolysosomes, particularly the unsaturated fatty acids (UFAs). Functionally, deletion of Qki and inhibition of UFA biosynthesis both decrease endolysosome-mediated receptor degradation, thereby enriching receptors on the cytoplasmic membrane (e.g., Frizzled and Notch1) that are essential for maintaining stemness. This enrichment of receptor signaling enables GSCs to cope with the low ligand levels during their invasion. On the other hand, lower lysosomal activity induced by Qki deletion and UFA loss led to defective mitophagy. We also found that insufficient UFAs in mitochondrial membrane significantly compromised mitochondrial membrane integrity and function. These two mechanisms concomitantly led to accumulation of damaged mitochondria and higher levels of reactive oxygen species (ROS), and consequently genomic instability. Lastly, we found that the higher level of genomic instability induced by Qki loss rendered cells more sensitive to anti-CTLA4 and anti-PD1 antibodies. Taken together, our data suggest that Qki/UFA loss-induced endolysosomal and mitochondrial defects promote gliomagenesis yet render cells vulnerabilities that could be harnessed for therapeutic purposes.